SISTEM PENDUKUNG KEPUTUSAN PENENTUAN KARYAWAN DENGAN METODE TOPSIS - Ameliawati; Ayu Adellia Zalianty; Nadira Putri Hermawan; Emi Sita Eriana (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
This research aims to develop a decision support system that supports the appointment process of permanent employees from contract employees using the TOPSIS method. Given the importance of having quality human resources, an objective and efficient selection process is needed to ensure the quality of employees. The criteria used in this research include attendance, performance, discipline, loyalty, offense, length of service, and last level of education. The TOPSIS method was chosen due to its ability to analyze alternatives based on distance to positive and negative ideal solutions. The evaluation results show that this system can provide appropriate recommendations in determining employees who are eligible to be appointed as permanent employees, with a high level of accuracy. This research concludes that the application of a TOPSIS-based decision support system is very effective and recommended for use in the employee selection process in a corporate environment.